Sanitary and hygienic characteristics of potassium stearate as a source of anthropogenic pollution of water reservoirs - Lototska , O.V.; Krytska , H.A.; Kucher , S.V. (Medicni Perspektivi, 2022)
Monitoring of surface water quality indicates deterioration of its quality due to anthropogenic pollution. Among them, potassium stearate (PS) occupies a prominent place. The purpose of the study is to substantiate regulations of potassium stearate in the water of reservoirs on the basis of sanitary and hygienic assessment of potassium stearate, study its stability and transformation, the impact on the organoleptic properties of water, the sanitary condition, self-cleaning processes and the sanitary condition of reservoirs. Research methods – bibliographic, analytical, statistical, sanitary and hygienic. It was found that the average effective concentration of PS by taste for the threshold of sensation (1 point) was at the level of 6.43 mg/dm3. The intensity of the taste of 1-2 points was maintained for 10 days. Potassium stearate is a hydrolyzing and non-chlorinating substance. As a result of assessing the impact of potassium stearate on the processes of self-purification of water from organic pollution by observing the dynamics of water oxidation, dissolved oxygen concentration and biochemical oxygen demand (BOD), the processes of ammonification, nitro- and nitrification, it was found that the limiting potassium stearate for reservoirs is BOD. On the basis of threshold and inactive concentrations by all limiting signs of harmfulness one allows recommending the maximum permissible concentration for potassium stearate at the level of 0.25 mg/dm3. The limiting indicator of harm is sanitary. Comprehensive assessment of the obtained experimental and calculated data by the hygienic rationing of PS in general the water of open reservoirs allows classifing it as the 4th class of danger (practically non-toxic substances).